ASR, Volume 20, n° 1, 2016 - Full Issue - journal system (African Sociological Review, 2016)
Contents Editorial .................................................1 General Issue A Case for ‘Prevailing Ecology’ as Premium Determinant in Home-Based Child Care Conceptualisation and Measurements Peter Atakuma Agbodza ..................................................2 Research Papers Une histoire particulière de la mondialisation : Technique, travail et industrialisation de la noix de cajou au Mozambique 20 Fernando Bessa Ribeiro .................................................20 Gender Issues in human trafficking incidents in Edo State Nigeria Clementina O. Osezua ................................................36 Joint Ownership of family land in Uganda: Examining the responses, challenges and policy implications Robert Kabumbuli ....................................................67 L’embouteillage dans les Grandes villes de L’Afrique de L’Ouest et ses problems: Cas de Cotonou au Benin Offin Lié Rufin Akiyo, Julien Adounkpe, Charles Lambert Babajide, Ikililou Akobi & Benoît N’bessa .....................87 Gender and Corruption in Nigerian Politics: An exploratory case study Amaechi D. Okonkwo .................................................111 Militantisme Politique et Entrepreneuriat :: relations de dépendance et enjeux dans le contexte Camerounais Valentin Ngouyamsa ............................................137